LAMA PEMBERIAN SEMEN IONOMER KACA (SIK) BERLAPIS TERHADAP KEKUATAN TEKAN TUMPATAN - Sanda Astrinata; Sri Ediati; Almujadi Almujadi (Poltekkes Kemenkes Yogyakarta, 2014)
Restorative material replacing teeth that have been damaged,GIC must be able to withstand the compressive forces ofmastication. Objective to determine to determine the effect ofduration of layered glass ionomer cement on the compressivestrength. The method is laboratory experiments withposttest only control group design. The population are 20 premolarteeth. Samples were taken from a population with asaturated sampling techniques. Samples were divided intofour groups, namely group A with a duration of 1.5 minuteslayered GIC, duration of group B 2 minutes, duration of groupC 3 minutes, and group D 2 minutes without layered applicationas a control. The research variable is compressivestrength and were analyzed using anova test with significancylevel of 0.05. Based on the statistic test obtained p-value = 0.336. There was not effect between duration of glass ionomercement layered application and compressive strength.